2023
DOI: 10.1172/jci.insight.166485
|View full text |Cite
|
Sign up to set email alerts
|

Combined molnupiravir-nirmatrelvir treatment improves the inhibitory effect on SARS-CoV-2 in macaques

Abstract: The periodic emergence of SARS-CoV-2 variants of concern (VOCs) with unpredictable clinical severity and ability to escape preexisting immunity emphasizes the continued need for antiviral interventions. Two small molecule inhibitors, molnupiravir (MK-4482), a nucleoside analog, and nirmatrelvir (PF-07321332), a 3C-like protease inhibitor, have recently been approved as monotherapy for use in high risk COVID-19 patients. As preclinical data are only available for rodent and ferret models, we here assessed the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Overall, our study identified five hotspot residues located at the drug-binding site of nirmatrelvir that warrant close monitoring in the clinical setting. The results also call for the development of the next generation of M pro inhibitors with a high genetic barrier to drug resistance or combination therapy to reduce the incidence of resistance …”
Section: Discussionmentioning
confidence: 99%
“…Overall, our study identified five hotspot residues located at the drug-binding site of nirmatrelvir that warrant close monitoring in the clinical setting. The results also call for the development of the next generation of M pro inhibitors with a high genetic barrier to drug resistance or combination therapy to reduce the incidence of resistance …”
Section: Discussionmentioning
confidence: 99%
“…In virtue of pre-clinical studies suggesting a synergistic effect of antiviral combinations [6] , [7] , [8] , [9] , an off-label combination regimen of molnupiravir (800 mg q 12 hours) and nirmatrelvir/ritonavir (300/100 mg q 12 hours) was started (day 64). Five days later (day 69), antigenic testing on NPS resulted negative, nonetheless, the treatment was still carried out until day 73.…”
Section: Case Reportmentioning
confidence: 99%
“…Regarding in vivo models, the combination of molnupiravir plus nirmatrelvir was evaluated in two studies in mice and macaques, while one study evaluated molnupiravir in association with the parent nucleoside of remdesivir (GS-441524) in hamsters [ 6 , 7 , 14 ]. In macaques infected with the SARS-CoV-2 Delta variant, co-administration of molnupiravir and nirmatrelvir reduced viral shedding, virus replication in the lower respiratory tract, and viral antigen in respiratory tissues, but no definitive results were achieved regarding its safety and tolerability [6] .…”
Section: Scoping Reviewmentioning
confidence: 99%
“…As reflected in Figure A, the attention weights highlight the nitrile group, dimethylcyclopropylproline (DMCP) group, tert-butyl group, and trifluoroacetyl group of PF-07321332, which is a second-generation orally available SARS-CoV-2 Mpro inhibitor developed by Pfizer and has been studied in vitro and in the clinical phase (NCT04756531, NCT04960202, and NCT05011513). The substructures stressed by attention mechanism are highly in accordance with the inhibitory mechanism according to the crystal structure of SARS-CoV-2 Mpro in complex with PF-07321332 determined by Zhao and co-workers .…”
Section: Resultsmentioning
confidence: 99%